Pengaruh Pemotongan Daun dan Pemberian Konsentrasi Ekstrak Bawang Merah terhadap Pertumbuhan Setek Kopi Robusta (Coffea canephora P.) - I GEDE BUDI YUDA KUMARA; I WAYAN PASEK ARIMBAWA; I NYOMAN SUTEDJA (Fakultas Pertanian Universitas Udayana, 2020)
Effect of Leaf Cutting and Concentration of Shallot Extract on the Growth of Cuttings Robusta Coffee (Coffea canephora P.). Robusta coffee plants (Coffea canephora P.) in general can be reproduced generatively by seeds, while the vegetative method can be done by grafting, cuttings, and tissue culture. Breeding of robusta coffee by generative method was often unsatisfactory, therefore the propagation of Robusta coffee is recommended using vegetative methods, namely cuttings. This study aims to determine the effect of leaf area cutting and the concentration of shallot extract and its interaction on the growth of Robusta coffee cuttings. This study used 2 factors in factorial design, namely: percentage of leaf cutting and the concentration of shallot extract. Variables observed were shoots growth time, shoots length, shoots diameter, number of leaves of seedling, leaf area of ??seedling, number of primary roots, length of primary root, oven dry weight of the root, oven dry weight of shoots, leaf oven weight, photosynthetic partition coefficient and total dry weight of plants.The results of this study showed that the best growth of Robusta coffee cuttings was shown in the 0% leaf cutting treatment with the heaviest total dry weight of the seedlings, which was 4.35 g and experienced an increase of 131.38% compared with 75% leaf cutting. Interaction of 0% leaf cutting by giving the concentration of onion extract 25% is the best treatment, this can be seen from the observation of the primary root length, but the total oven dry w eight showed no significant difference.